Mycobacterium tuberculosis Rv3802c encodes a phospholipase/thioesterase and is inhibited by the antimycobacterial agent tetrahydrolipstatin. - Sarah K Parker; Robert M Barkley; John G Rino; Michael L Vasil (PLoS ONE, 2009)
The cell wall of M. tuberculosis is central to its success as a pathogen. Mycolic acids are key components of this cell wall. The genes involved in joining the alpha and mero mycolates are located in a cluster, beginning with Rv3799c and extending at least until Rv3804c. The role of each enzyme encoded by these five genes is fairly well understood, except for Rv3802c. Rv3802 is one of seven putative cutinases encoded by the genome of M. tuberculosis. In phytopathogens, cutinases hydrolyze the waxy layer of plants, cutin. In a strictly mammalian pathogen, such as M. tuberculosis, it is likely that these proteins perform a different function. Of the seven, we chose to focus on Rv3802c because of its location in a mycolic acid synthesis gene cluster, its putative essentiality, its ubiquitous presence in actinomycetes, and its conservation in the minimal genome of Mycobacterium leprae. We expressed Rv3802 in Escherichia coli and purified the enzymatically active form. We probed its activities and inhibitors characterizing those relevant to its possible role in mycolic acid biosynthesis. In addition to its reported phospholipase A activity, Rv3802 has significant thioesterase activity, and it is inhibited by tetrahydrolipstatin (THL). THL is a described anti-tuberculous compound with an unknown mechanism, but it reportedly targets cell wall synthesis. Taken together, these data circumstantially support a role for Rv3802 in mycolic acid synthesis and, as the cell wall is integral to M. tuberculosis pathogenesis, identification of a novel cell wall enzyme and its inhibition has therapeutic and diagnostic implications.